Organ donation in Brazil: individual autonomy versus family consent - Faria, Gabriela Favaro; Granato, Marcelo de Azevedo; Pêgo-Fernandes, Paulo Manuel (São Paulo Medical Journal, 2026)
Brazil has the largest public transplantation system worldwide. Nevertheless, approximately 3,000 people die annually while on the organ waiting list, highlighting the difficulty of balancing the growing demand with the limited donation rate.